Trust on Tradition/Customs of Batu Bara Community in the 19th Century - Muhammad Faishal; Syahrin Harahap; Amroeni Drajat (Budapest International Research and Critics University, 2019)
This article discussed the trust in the traditions / customs of Batu Bara people in the 19th century. Batu Bara is one of the regions in North Sumatera Province, Indonesia. In the 19th century Batu Bara communities were dominated by Malay ethnic groups and popularly referred to as